Analysis on the dynamics and structure of scientific and innovation-information development indicators of the Russian federal districts - S. V. Sidorenko; T. A. Pershina; M. A. Khatuntseva; A. R. Bikbaeva (Вестник университета, 2023)
The factor of scientific and innovation-information development of the country has a significant impact on the level of its economic security. The article presents an analysis of science, innovation and information systems development in Russia, as they are one of the most important factors of the economic security of the state. An assessment of the leading and lagging regions in terms of innovation activity of organisations and volume of research and development was made. Also, directions for development were identified which require additional detailed study of science, innovation and information systems development at the level of federal districts with respect to their specific features and implementation of national projects. The obtained data are the basis for further assessment of the Russian economic security level within the framework of the National Security Strategy.